First visit of the mother in the newborn intensive care unit: the reception as promotion of human care - Eloah de Paula Pessoa Gurgel; Karla Maria Carneiro Rolim (Rev Rene)
When babies are separated from their mothers in order to be treated in a Newborn Intensive Care Unit, the mothers feel unhappy, afraid and stressed. The aim of this study is to analyze the mothers’ reactions towards seeing their babies in a Newborn Intensive Care Unit, and to know what their expectations are on the recovery, in order to propose the development of a support group for the mothers to help them go through the first visit and the stay of their babies during treatment. This is a descriptive-investigatory study with a qualitative approach, which took place in a Newborn Intensive Care Unit of a public maternity hospital in Fortaleza-Ce. The research subjects were mothers who had their babies hospitalized from August to September of 2004. Data analysis resulted in the following categories, which were extracted from the subjects’ discourse: expectations, reception, and first visit to the unit. We concluded that the nurses must have a differentiated perception of the first visit and of the babies’ stay in the unit, emphasizing its importance to the babies’ recovery and to their return to the family.